2021
DOI: 10.3390/jmse9060582
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Cross-Shore Shoreline Change on Multiple Timescales and Their Interactions

Abstract: In this paper, a new approach to model wave-driven, cross-shore shoreline change incorporating multiple timescales is introduced. As a base, we use the equilibrium shoreline prediction model ShoreFor that accounts for a single timescale only. High-resolution shoreline data collected at three distinctly different study sites is used to train the new data-driven model. In addition to the direct forcing approach used in most models, here two additional terms are introduced: a time-upscaling and a time-downscaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The relatively short time scale of 20 days encompasses that of winter monsoon pulses [28], on which the model can now focus more optimally. This is in line with the multi-scale approach of ShoreFor developed in [17,41], but within a simpler formulation. Figure 11c also shows that the seasonal fluctuation of the longshore contribution is now more pronounced than in the previous calibration (Figure 10c).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The relatively short time scale of 20 days encompasses that of winter monsoon pulses [28], on which the model can now focus more optimally. This is in line with the multi-scale approach of ShoreFor developed in [17,41], but within a simpler formulation. Figure 11c also shows that the seasonal fluctuation of the longshore contribution is now more pronounced than in the previous calibration (Figure 10c).…”
Section: Discussionsupporting
confidence: 79%
“…During summer monsoons, the small wave forcing leads to a small Ω eq , very similar to the instantaneous Dean number Ω, so that the disequilibrium Dean number is small and induces a small shoreline variation. This suggests that an intra-seasonal memory decay is not appropriate for summer conditions and a multi-scale approach should be considered [17,41]. Alternatively, here, the definition of Ω eq is re-valuated for summer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ibaceta et al (2020) suggested an ensemble Kalman Filter assimilation technique could track changes in model structure due to changing wave-shoreline feedback. Montaño et al (2021) and Schepper et al (2021) separately proposed two different multi-scale model approaches. Montaño et al (2021) used a Complete Ensemble Empirical Mode Decomposition method that linked different timescales of forcing to the corresponding timescales in the shoreline change.…”
Section: Timescales Of Changementioning
confidence: 99%
“…Montaño et al (2021) used a Complete Ensemble Empirical Mode Decomposition method that linked different timescales of forcing to the corresponding timescales in the shoreline change. In contrast, Schepper et al (2021) included upscaling, downscaling and direct forcing methods to link forcing to various timescales of shoreline evolution. These advances hint at ways forward to robustly predict future shoreline changes in a changing and uncertain climate using these simplified reduced complexity models.…”
Section: Timescales Of Changementioning
confidence: 99%